Educação para a saúde: um estudo de caso em curso supletivo - Jorge, Ana Emilia Smith (1983)
Health education pretends educating the persons in the way to make them capable to recognize their necessities in terms of health and, at the same time, to develop the sense of responsibility in the adoption of conscient means that may contribute for the promotion and maintenance of individual and collective health. programs of health education, also admitted as a contribution to obtain sanitary indexes which characterized physical, mental and social welfare of populations, rarely are elaborated and executed by the education 'and health organs. They are important when considered in relation of the economic and social development and as an educative form in health, through the analyses of its objectives and contents, which resulted as the application of a project. Studied in the school-system, in supplementary courses, and ·in relation of the curriculum adopted by schools, the results demonstrated that programs for heal the education fulfill a hiatus existing in this area, also in curriculum programs adopted by official teaching institutes.